The Archontic Holmes: Understanding adaptations of Arthur Conan Doyle's Sherlock Holmes stories in the context of Jacques Derrida's “Archive” (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2012)
A consideration of Sir Arthur Conan Doyle's Sherlock Holmes detective stories and their subsequent adaptations reveals a complex web of interdependency, which is in keeping with Jacques Derrida's concept of the archive, and can be extended to describe the functions and relations of all texts, not just those that claim explicit inter-relations.